Why people avoid prescribed medical treatment in India? - Shivendra Sangar; Varun Dutt; Ramna Thakur (Wolters Kluwer Medknow Publications, 2019)
Avoidance in seeking prescribed medical treatment can result in adverse consequences. The study was conducted to find out the reasons to avoid prescribed medical treatment and associations with various socioeconomic variables in India. Data from the National Sample Survey Organisation 71st Round on "Key Indicators of Social Consumption: Health" (January and June 2014) have been used. Variables such as place of residence, social categories, religion, and socioeconomic status have been used to study the associations with the various reasons to avoid prescribed medical treatment. Nonseriousness about the ailment was found to be the primary reason for not seeking prescribed medical treatment. Lack of availability of medical facility, long-waiting time, and financial constraints were other important reasons. Understanding the socioeconomic differentials among the reasons why people avoid prescribed medical treatment is critical in improving the effectiveness of health-care facilities in India.